Truck Drivers’ Road Traffic Accidents : Concealed Risk - Chuenwattana, Prakong (Journal of Health Science of Thailand, 2019)
This qualitative study was aimed at improving understanding of the constructed mindsets andexperiences of truck drivers’ risks about road traffic accidents as well as contextual conditions in-stilling the mindsets and experiences, especially conditions of truck drivers’ socio-cultural back-ground, economy, and everyday life experiences, as well as transportation and accident insurancesystems. Qualitative research procedures applied in this research were in-depth interviewing tech-nique and non-participatory observation with 17 truck drivers as sample informants. It was found in that road traffic accidents in a truck drivers’ experience were regarded as some-thing that could not be prevented and became normal. Truck drivers’ work patterns combined withexhaustion, time competition and regular experiences with traffic accidents allowed truck drivers tocome to terms with the accidents which were involuntarily difficult to avoid. Although accidents intruck drivers’ opinions were serious, the severity did not directly affect their lives because they,themselves, were protected by a physical size of the truck as well as structural contexts of thetransportation business and insurance deals with all accidents related problems. As a result, acci-dents could not bring about any negative consequences on truck drivers. This study suggests that a solution to road traffic accidents should not be focused only onindividuals, but government and concerned officials should also implement structural measures tochange individuals’ behaviors and mindsets to something different from their existing ones. In otherwords government officials’ corruption should be negated inorder to strictly implement concernedlaws as well as better controls and ethics of private business, particularly shady ‘deals’ cut betweentransportation business and insurance companies.